CFD IMPLEMENTATION FOR PRACTICAL SIMULATION OF MULTIPHASE REACTIVE FLOW ON INDUSTRIAL SWIRL FLAME BURNERS - Klančišar, Marko (Journal of Energy Technology, 2024)
This paper investigates the characteristics of non-premixed combustion, carbon monoxide emission and flame geometry with a comparison of 18- and 22-MW NO x reduced (NR) and swirl flame (1SF) burners mounted on a 20-MW hot water boiler on two essentially different fuel types. The simulated results indicate that with implementation of swirl technology, no unsteadiness of a flame burnout can be detected. Furthermore, the high mixing energy increases the reactive capability of a mixed phase on both the oil and gas fuels used in the process. With the increase of secondary air swirl strength, the flamelet or jet area tends to be greater, and the circular flow of high temperature flow gas is enhanced. The flame tends to be shorter and wider. However, the capability to adjust a 1SF burner to different boiler geometries is closely combined with flame stabilization and flue gas emissions; therefore, the right flame geometry is determined by various CO emissions throughout flame region. With turbulence intensity, the flame length was reduced by approximately 55% without a loss of reactive stability. As for the increased swirl ratio, a recirculation flow in flame core also increases parallel to it, thereby reducing the flame core temperature, hence decreasing the thermal NO x build.
Keywords: CFD; Multicomponent flow; Turbulent flow; Combustion; Industrial burner